The Indirect Effect of Distress Tolerance on Young Adult Alcohol Use Behaviors via Coping Motives - Wahesh, Edward (Journal of addictions & offender counseling, 2020)
We examined the indirect effect of distress tolerance on alcohol use and problems via drinking-to-cope motives within a national sample of young adults (N = 297). Analyses suggested coping motives mediated the relationship between distress tolerance and drinking.